A new type of WC–Co–Ni–Al cemented carbide: Grain size and morphology of γ′-strengthened composite binder phase. (1st January 2017) - Long, Jianzhan; Zhang, Weibin; Wang, Yaru; Du, Yong; Zhang, Zhongjian; Lu, Bizhi; Cheng, Kaiming; Peng, Yingbiao
Abstract: In contrast to the much larger grain size of the binder phase in traditional WC–Co cemented carbide, we have achieved a significantly reduced grain size of the γ′-Ni3 Al strengthened composite binder phase in WC–Co–Ni–Al cemented carbide. Based on thermodynamic calculations, decisive experiments and microstructure characterizations, the formation mechanism for grain size of binder phase in WC–Co–Ni–Al cemented carbide has been clarified, and the related boundary morphology and performance characteristics are discussed. Graphical abstract: